Opportunities to Set Up Entrepreneurial Service Businesses (Case of Masjed Soleyman Township) - Hossein Mehdizadeh; Nematollah Shiri; Mohammad Hossein Mohmedi Kartalaei (آموزش و مدیریت کارآفرینی)
The general purpose of this study was to identify the opportunities for setting up entrepreneurial service businesses in Masjed Soleyman Township. To achieve this goal, the qualitative paradigm and the Delphi method were used. The community studied in this research included experienced entrepreneurs, specialists, pundits, and other experts in the fields of service entrepreneurship in Masjed Solyman Township, from which 21 were selected as members of the Delphi panel using the snowball sampling method. In this study, after three rounds of investigation, a consensus was reached regarding the opportunities for starting entrepreneurial businesses. The main research tool in the first round of the Delphi study was a questionnaire with open-ended questions and in the second and third rounds, a questionnaire with closed and open-ended questions. In the first round, the data were analyzed using the continuous comparison method. In the second round, data analysis was done by drawing the frequency distribution table (percentage and cumulative percentage) using SPSS software version 27. In the third round, data analysis was done by drawing the frequency distribution table (percentage and cumulative percentage) and calculating the percentage of agreement (CVI) and Kendall agreement coefficient. In addition, the mean and standard deviation were used to prioritize the types of opportunities for setting up entrepreneurial service businesses. According to the results, the most important opportunities for starting entrepreneurial service businesses in Masjed Soleyman Township include "packaging of livestock products such as curd and other similar products"; "packaging of various medicinal plants"; "cold storage of agricultural and food products"; "production, packaging, and distribution of local bread"; and "honey packaging". This study provides policymakers and planners with practical suggestions.